What went wrong? : Western impact and Middle Eastern response - Lewis, Bernard, 1916- (New York Oxford University Press, 2002)
"For many centuries, the world of Islam was in the forefront of human achievement - the foremost military and economic power in the world, the leader in the arts and sciences of civilization. Christian Europe, a remote land beyond its northwestern frontier, was seen as an outer darkness of barbarism and unbelief from which there was nothing to learn or to fear. And then everything changed, as the previously despised West won victory after victory, first on the battlefield and in the marketplace, then in almost every aspect of public and even private life." "In this volume, Bernard Lewis examines the anguished reaction of the Islamic world as it tried to understand why things had changed, how they had been overtaken, overshadowed, and to an increasing extent dominated by the West. Lewis provides a fascinating portrait of a culture in turmoil. He shows how the Middle East turned its attention to understanding European weaponry and military tactics, commerce and industry, government and diplomacy, education and culture. He describes how some Middle Easterners fastened blame on a series of scapegoats, both external and internal, while others asked, not "who did this to us?" but rather "where did we go wrong?" and, as a natural consequence, "how do we put it right?" Lewis highlights the striking differences between the Western and Middle Eastern cultures from the eighteenth to the twentieth centuries with thought-provoking comparisons of such things as Christianity and Islam, music and the arts, the position of women, secularism and the civil society, the clock and the calendar."--Jacket
The lessons of the battlefield -- The quest for wealth and power -- Social and cultural barriers -- Modernization and social equality -- Secularism and the civil society -- Time, space, and modernity -- Aspects of cultural change
Includes bibliographical references and index
Keywords: Middle East -- History -- 1517-; History